Gregor Mendel - the scientist based on primary sources 1822-1884 - Matalová, Anna; Matalová, Eva (Springer biographies, 2022)
The major purpose of this book is to present Johann Gregor Mendel (1822-1884) in a real and interesting way based on the most recent historical research and analysis of authentic sources. The authors aim to show Mendel's scientific thinking and inner feelings together with his environment and to communicate his message as a multifaceted personality and modern experimentalist.The book draws from the only existing short sketch of Mendel's youth, his letters and the biographical ceiling paintings that were made according to his proposal. They form the basis of the self-portrait concept.The structure of the book follows thematic groups covering Mendel's activities from a poor village boy in search for education and financial security, as not being physically suitable for running his father's farm. The book does not perpetuate the myths invented by some creative authors to make Mendel's biography more attractive. Mendel's life and work are dramatic enough without those embellishments. Mendel found happiness in science and he was able to explain the theory of new scientific facts. He was not a tragic figure, he did not work to become famous, but to be useful. His pea research has now been appreciated as a genius accomplishment of a scientist.The book is published at the occasion of Mendel's birthday bicentennial